PERAN PEREMPUAN DALAM UPACARA RAMBU SOLO’ DI LEMBANG PITUNG PENANIAN KECAMATAN RANTEBUA KABUPATEN TORAJA UTARA - Bunga, Hanna Toban; Kawung, Evelin J. R.; Kandowangko, Nicolaas (Universitas Sam Ratulangi, 2020)
This study aimed to explain about the role of women inRambu solo ritual procession at Pitung Penanian village, Rantebua district, Toraja Utara regency. The author used qualitative research method that carried out by descriptiveits given concept and explanation properly about role of womenin rambu solo ritual procession at Toraja Utara and supported by primer data andsecondary data. Data collect technique that used was interview and observation. The result of the study shown that procession of Rambu solo ritual atTondon Mamullu village, Makale district, Toraja Utara regency from thepreparation, implementation until the funeral procession, the women also play arole and contribute. it can be shown by offering few of buffalos and pigs, andsome given groceries. The women also participated in family meeting to talkabout the heirs, the degree of tne ritual that will be held, the place of the ritual andprovide sacrificial animals. The roles of women such as: ma’tumbukki, ma’papangngan and ma’pairuk, pa’katia’, pa’marakkaKeyword : Role, Rambu Solo’, Ritual